2014 IEEE/RSJ International Conference on Intelligent Robots and Systems 2014
DOI: 10.1109/iros.2014.6942696
|View full text |Cite
|
Sign up to set email alerts
|

Human control of robot swarms with dynamic leaders

Abstract: Abstract-The study of human control of robotic swarms involves designing interfaces and algorithms for allowing a human operator to influence a swarm of robots. One of the main difficulties, however, is determining how to most effectively influence the swarm after it has been deployed. This may be necessary in a environmental exploration task where areas of interest arise dynamically, and thus the human operator needs to guide the swarm to explore them. Past work has focused on influencing the swarm via static… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 13 publications
0
25
0
1
Order By: Relevance
“…This is no different conceptually from the usual setting of an autonomous swarm, since it involves the human acting essentially outside the algorithmic loop. It has been argued that humans are able to guide a swarm better using a dynamic set of leaders [143], as compared to manipulating a fixed leader. There is also evidence which suggests that human operators can adapt their handling of (virtual) leaders to guide large swarms through obstacle-rich environments in a better manner than built-in, standard flocking rules [144].…”
Section: E External Control Of Aerial Swarmsmentioning
confidence: 99%
“…This is no different conceptually from the usual setting of an autonomous swarm, since it involves the human acting essentially outside the algorithmic loop. It has been argued that humans are able to guide a swarm better using a dynamic set of leaders [143], as compared to manipulating a fixed leader. There is also evidence which suggests that human operators can adapt their handling of (virtual) leaders to guide large swarms through obstacle-rich environments in a better manner than built-in, standard flocking rules [144].…”
Section: E External Control Of Aerial Swarmsmentioning
confidence: 99%
“…Here, the authors found that the explicit method gave human operators better control over the swarm, but hypothesized that the tacit method could be more robust to sensing error if a larger percentage of the swarm were leader robots, to allow for faster propagation of used intent. In [119] and [120], the authors further this work by presenting an algorithm for selecting multiple leaders dynamically in a swarm as the topology of the communication graph changes. They found that, while the explicit method of propagation was again superior overall, the tacit method performed better under significant sensing error.…”
Section: Persistent Influence Via Leadersmentioning
confidence: 99%
“…The technique proposed in [183] consists in taking control of one robot in the swarm, transforming it in an avatar, so that local modifications obtained with a changed behavior of the avatar are transferred gradually to the rest of the swarm. A similar method is used by Walker et al [184], who investigated how a swarm can be controlled by dynamically selecting leader robots and guiding their movement. Kolling et al [185] proposed two types of interaction, called intermittent and environmental : the first type consists in selecting individual robots to make them switch from their current behavior to a new behavior; with the second type, users manipulate a local characteristic of the environment in order to induce a new behavior in robots located in the nearby area.…”
Section: Human-swarm Interactionmentioning
confidence: 99%